Multimodal user interaction methods for virtual reality headsets - Pallavi, Mohan (Nanyang Technological University, 2020)
Despite the popularity of VR, there is a lack of research in interaction methods for VR HMDs. In their confined setting, conventional VR headsets provide only limited input modalities. Commonly-supported interaction methods include tracking the user's head orientation, external controllers and buttons, and more recently, gaze interaction by eye tracking. This research aims to widen the currently available range of input modalities in virtual reality, by developing novel interaction designs and exploring multimodal interaction in mobile VR.